(untitled) (Emergent: Journal of Educational Discoveries and Lifelong Learning (EJEDL), 2023)
This article describes in detail the impact of communicative teaching on students in English language teaching, innovative processes in the field of English language teaching, communicative competence, one of the main tasks specified in the educational system program.